E-LEARNING TRAINING TO OPTIMIZE TEACHING LEARNING PROCESSES FOR TEACHER MATHEMATICS SMK KOTA LANGSA - Fitra Muliani; Amelia Amelia; Ulya Nabila; Nurviana Nurviana; Riezky Purnamasari (Global Science Society, 2021)
The education system, from elementary to tertiary levels, has implemented sophisticated technology-based learning methods, which requires us to survive. IT-based learning is needed in this regard, especially during the current Covid-19 pandemic. In addition, based on an appeal from the government, the learning process is carried out by applying the distance method, which can be done by utilizing technology, namely E-Learning media such as google classroom and zoom. As for the purpose of service through training for Mathematics teachers of Langsa City Vocational High School, namely to help in problems related to distance learning. The method used is the direct approach method, lectures and practicum. The approach method is carried out by observing teacher problems related to the difficulties and lack of use of E-learning media. The lecture method is carried out by providing tutorials to the teacher on the use of E-learning media, then followed by practicum. The results of this service are very good, it can be seen from the participation and enthusiasm of the teacher in participating in this activity then the teacher is able to use online learning media. This service is expected to contribute to mathematics teachers, especially the Langsa City Vocational School teachers, in the distance learning process by utilizing google classroom and zoom.